2015
DOI: 10.1017/s1431927615015020
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Analysis of In Vivo Hypoglycemiant Effect of Two Polyoxometalates in Rats with Streptozotocin-Induced Diabetes

Abstract: Two polyoxometalates (POMs), synthesized through a self-assembling method, were used in the treatment of streptozotocin (STZ)-induced diabetic rats. One of these nanocompounds [tris(vanadyl)-substituted tungsto-antimonate(III)-anions—POM1] was previously described in the literature, whereas the second [tris-butyltin-21-tungsto-9-antimonate(III)-anions—POM2], was prepared by us based on our original formula. In rats with STZ-induced diabetes treated with POMs (up to a cumulative dose of 4 mg/kg bodyweight at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 77 publications
(110 reference statements)
0
15
0
1
Order By: Relevance
“…These ndings are in agreement with previously published similar effects obtained for the animals (rats and mice) treated with various other polyoxotungstates. 7,9,19 In addition, both studied polyoxotungstates (20 mg per kg per day, 14 days) did not affect the serum glucose concentration in the healthy rats (Fig. 3).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…These ndings are in agreement with previously published similar effects obtained for the animals (rats and mice) treated with various other polyoxotungstates. 7,9,19 In addition, both studied polyoxotungstates (20 mg per kg per day, 14 days) did not affect the serum glucose concentration in the healthy rats (Fig. 3).…”
Section: Discussionmentioning
confidence: 79%
“…The obtained hypoglycemic effect of the investigated polyoxotungstates is in agreement with previously published in vivo studies that reported effective hypoglycemic actions of various types of polyoxotungstates on different diabetic animal models. [7][8][9] According to literature, a few putative mechanisms of POM induced normoglycemic action were indicated: a-glucosidase activity inhibition that consequently results in the reduced absorption of intestinal carbohydrates, 8 insulin mimetic effects including glucose uptake stimulation and lipolysis inhibition, 27 prevention of STZ-induced apoptosis of pancreatic b-cells, and stimulation of insulin synthesis. 7 Moreover, some polyoxotungstates were found to prevent the development of diabetic life-threatening microvascular and macrovascular complications by signicant limitation of aldose reductase activities and accumulation of advanced glycation end products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypoglycemic potential of various vanadium compounds has also been examined in models that present features similar to those observed in types 1 and 2 diabetes mellitus. In models that resemble type 1 diabetes, administration of polyoxovanadates (e.g., decavanadate) improves serum glucose levels and glucose tolerance, albeit the insulin deficiency improvement has been demonstrated in a limited number of studies [92,[280][281][282][283][284][285][286]. Indeed, decavanadate has demonstrated to be more efficient than BMOV in inducing glucose uptake in rat adipocytes [287].…”
Section: Vanadium Anti-diabetic Compounds In Animal and Human Modelsmentioning
confidence: 99%
“…Therefore, in both diabetic animals and humans, the administration of vanadium decreases the hepatic glucose production [284,285,312], although discrepancies in this respect still exist [45,268,269,288,289]. Finally, the direct biochemical control of glucose homeostasis for vanadium treatments is associated with the enhancement in glycolysis and glucose oxidation as observed in isolated rat adipose tissue and hepatocytes HepG2 cells [17,281,301,313].…”
Section: Vanadium and Carbohydrates Homeostasis In Type 2 Diabetes Mementioning
confidence: 99%